Karakteristik Kimia dan Sensori Selai Buah Naga Merah (Hylocereus polyrhizus) dengan Penambahan Pektin - Makuku, Viorenska; Mailoa, Meitycorfrida; Palijama, Syane (Jurnal Agrosilvopasture-Tech, 2025)
This study aims to determine the effect of adding pectin to the chemical and sensory characteristics of red dragon fruit (Hylocereus polyrhizus) jam. The study used a completely randomized design. one factor consisting of 5 levels of pectin addition treatment including control (without the addition of pectin), 1.5 g, 2 g, 2.5 g and 3 g. The results of the study concluded that the addition of pectin had a very significant effect on water content, total sugar, vitamin C, pH, taste, texture and over all, while it had no significant effect on the ash content and color of red dragon fruit jam. red dragon fruit include water content 37.88–57.63%, ash content 0.70–0.83%, total sugar 21.13–26.47%, vitamin C 0.0227–0.0324%, pH 4.2–4.5 and sensory properties such as color (somewhat like–like), taste (dislike–somewhat like), texture (dislike–like) and over all (somewhat like–like).